Evaluasi Kolaborasi Puskesmas dengan LSM dalam Penanggulangan HIV pada Kelompok Risiko LSL di Puskesmas PDP Kota Mataram - Nila Imtihani; Menap Menap; Sabar Setiawan (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT HIV prevention among Men who have Sex with Men requires collaboration between primary health facilities and community-based organizations to overcome service access barriers and deeply rooted social stigma in society. Objective to evaluate the implementation, process, outcomes, and challenges of collaboration between Community Health Centers and Non-Governmental Organizations in HIV prevention among Men who have Sex with Men risk groups in Mataram City. Descriptive evaluative qualitative research using in-depth interviews, participatory observation, and documentation studies involving seventeen informants including Community Health Center heads, HIV program managers, Non-Governmental Organization staff, People Living with HIV/AIDS, and Health Office officials conducted during October to November 2025 at four Care Support and Treatment Community Health Centers. Collaboration functioned effectively and adaptively with complementary role division that improved service access, antiretroviral treatment adherence, and continuity of care for key populations. Coordination mechanisms combined informal and formal communication with a single-door reporting system through Community Health Centers. Main constraints included limited human resources, absence of standardized collaboration operational procedures, dependence on personal relationships, and persistent strong social stigma toward HIV. Collaboration proved effective in enhancing HIV program achievements but requires strengthening of institutional aspects, formal governance, and policy support to ensure long-term sustainability. Keywords: Community Health Center Collaboration, Non-Governmental Organizations, HIV Prevention.  ABSTRAK Penanggulangan HIV pada kelompok Laki-laki Seks dengan Laki-laki memerlukan kolaborasi antara fasilitas kesehatan primer dengan organisasi berbasis komunitas untuk mengatasi hambatan akses layanan dan stigma sosial yang masih mengakar di masyarakat. Tujuan mengevaluasi pelaksanaan, proses, hasil, dan tantangan kolaborasi Puskesmas dengan Lembaga Swadaya Masyarakat dalam penanggulangan HIV pada kelompok risiko Laki-laki Seks dengan Laki-laki di Kota Mataram. Penelitian kualitatif deskriptif evaluatif dengan teknik wawancara mendalam, observasi partisipatif, dan studi dokumentasi terhadap tujuh belas informan meliputi Kepala Puskesmas, penanggung jawab program HIV, petugas Lembaga Swadaya Masyarakat, Orang dengan HIV/AIDS, dan pejabat Dinas Kesehatan yang dilaksanakan pada periode Oktober hingga November 2025 di empat Puskesmas Perawatan Dukungan dan Pengobatan. Kolaborasi berjalan secara fungsional dan adaptif dengan pembagian peran komplementer yang meningkatkan akses layanan, kepatuhan pengobatan antiretroviral, dan keberlanjutan perawatan pada populasi kunci. Mekanisme koordinasi menggabungkan komunikasi informal dan formal dengan sistem pelaporan satu pintu melalui Puskesmas. Kendala utama meliputi keterbatasan sumber daya manusia, belum tersedianya Standar Operasional Prosedur kolaborasi yang baku, ketergantungan pada hubungan personal, dan masih kuatnya stigma sosial terhadap HIV. Kolaborasi terbukti efektif meningkatkan capaian program HIV namun memerlukan penguatan aspek kelembagaan, tata kelola formal, dan dukungan kebijakan untuk menjamin keberlanjutan jangka panjang. Kata Kunci: Kolaborasi Puskesmas, Lembaga Swadaya Masyarakat, Penanggulangan HIV.